Brazilian political parties according to scholars Analysis of an expert survey - Tarouco, Gabriela da Silva (2015)
The ideological positioning of the Brazilian political parties has been measured in several ways, which are discussed and compared. In addition, the current ratings are confronted with the results of a survey applied to Brazilian political scientists. The ideological classification resulting from the survey coincides with several others in the literature, compiled from different methods, which include evaluation by party members. The conclusion is that the location of Brazilian parties in the left-right dimension is quite uniform, among different measurements, to be considered valid, opposing the current evaluation of absence of political identity in the Brazilian party system.